2009
DOI: 10.1590/s0100-879x2009000400004
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics and structural adaptations of the rat femur after hindlimb suspension and treadmill running

Abstract: We microscopically and mechanically evaluated the femurs of rats subjected to hindlimb unloading (tail suspension) followed by treadmill training. Female Wistar rats were randomly divided into five groups containing 12-14 rats: control I (118 days old), control II (139 days old), suspended (tail suspension for 28 days), suspended-released (released for 21 days after 28 days of suspension), and suspended-trained (trained for 21 days after 28 days of suspension). We measured bone resistance by bending-compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“…In this study, hypoactivity secondary to three weeks of tail suspension effectively impaired bone quality, as shown by reduced bone mass, mechanical weakness, and deterioration of trabecular microarchitecture in suspended rats, when compared to the weight‐matched controls. These findings are in agreement with previous reports in literature, which state that hypoactivity due to hindlimb suspension quickly leads to osteopenia (Falcai et al, ; Shimano and Volpon, ). Our histological and BMD data showed severe trabecular bone loss caused by a relatively short duration of suspension.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, hypoactivity secondary to three weeks of tail suspension effectively impaired bone quality, as shown by reduced bone mass, mechanical weakness, and deterioration of trabecular microarchitecture in suspended rats, when compared to the weight‐matched controls. These findings are in agreement with previous reports in literature, which state that hypoactivity due to hindlimb suspension quickly leads to osteopenia (Falcai et al, ; Shimano and Volpon, ). Our histological and BMD data showed severe trabecular bone loss caused by a relatively short duration of suspension.…”
Section: Discussionsupporting
confidence: 94%
“…This is known as the Hueter-Volkman law (Figure 1(b)), which was further defined by Frost in the twentieth century and is often used by clinicians in surgical correction of certain limb deformities [4, 17]. Lack of mechanical loading also results in decreased bone formation, as shown by weightlessness and suspension experiments (Figure 1(a)) [1921]. …”
Section: Biomechanics Of the Musculoskeletal Systemmentioning
confidence: 99%
“…However, these studies were performed in different experimental environment (spaceflight) and were conducted in short unloading and reloading periods, so it is not appropriate to compare to our study. Some studies19,20 experimented the simulated weightlessness using the method performed in our study. They reported that the skeleton of growing rats is capable of a rapid recovery from the adverse effects of simulated weightlessness.…”
Section: Discussionmentioning
confidence: 99%